The Performance Effects of Congruence Between Product Competitive Strategies and Purchasing Management Design - David, Julie Smith; Hwang, Yuhchang; Pei, Buck K. W.; Reneau, J. Hal (Management Science, 2002)
The objective of this study is to examine a performance contingency effect between product competitive strategy and organization design using an archival approach. Specifically, this study examines a sample of 194 firms from 20 industries based on the data collected by Center for Advanced Purchasing Studies (CAPS) in its benchmarking surveys between 1989-1994 and links the benchmarking data to the COMPUSTAT (Standard & Poor's) financial data of these firms. The results of the study reveal a contingency relationship among product competitive strategies, purchasing design characteristics, and overall firm financial performance (return on assets). Specifically, the nature of this contingency relationship suggests that a firm's product competitive strategy must be enabled with a complementary design in purchasing management to promote firm performance. Given the growing practice of benchmarking at the functional level, this study also examines whether or not a firm achieving a congruency in product strategy and design will necessarily enjoy higher operational efficiency at the purchasing management level. The results show that this is true only under specific conditions. The implications of the preceding findings are discussed accordingly.